PDMS-coated porous PVDF hollow fiber membranes for efficient recovery of dissolved biomethane from anaerobic effluents - Sethunga, Godakooru Sethunga Mudiyanselage Dilhara Prebhashwari (2020)
This report demonstrates the fabrication of a composite hollow fiber membrane that efficiently recovers dissolved methane (dCH4) from anaerobic wastewater treatment effluents via membrane contactor (MC) process. We first fabricated highly porous hollow fiber membranes (∼85% porosity) using polyvinylidene difluoride (PVDF). Then, we coated the whole structure (bulk), or lumen side of PVDF supports with polydimethylsiloxane (PDMS), a hydrophobic polymer possessing high gas permeability. The adjustment of the concentration of PDMS precursor mix could effectively serve for tuning the performance characteristics of MC membranes and helped suppress membrane wetting, a major performance-reducing factor. Despite their denser skin layers, the lumen-modified membranes demonstrated superior dCH4 recovery flux. Mass transfer analyses have confirmed the importance of preserving bulk porosity while coating the membrane surfaces. The long-term performance tests performed using actual anaerobic effluents suggested that the PDMS coating did not accelerate fouling, such that the lumen-modified MC membranes showed an almost steady flux for 8 days with an anaerobic membrane bioreactor effluent. A high-strength effluent, obtained from an up-flow anaerobic sludge blanket reactor, induced faster fouling. However, we observed only a ∼20% flux decline in a 10-day operation. Thus, we propose that the designed PDMS-PVDF composite membranes are promising for industrial practices.